Philippines Quarterly Update, June 2011 : Generating More Inclusive Growth - World Bank (Manila, 2017)
The Philippines quarterly update provides an update on key economic developments and policies over the past three months. It also presents findings from recent World Bank work on the Philippines. It places them in a longer-term and global context, and assesses the implications of these developments and other changes in policy for the outlook for the Philippines. Its coverage ranges from the macro-economy to financial markets to indicators of human welfare and development. It is intended for a wide audience, including policy makers, business leaders, financial market participants, and the community of analysts and professionals engaged in the Philippines. Though the revised gross domestic product (GDP) growth estimates show small deviation from the old base year and methodology, the revision has resulted in a nominal GDP which is 6 percent larger and hence, lower fiscal statistics as a percentage of GDP (e.g., lower tax effort, but improved debt ratio), but also important sectoral growth changes. Investment is now noticeably higher due to improved coverage and transfer of items previously booked under consumption (e.g., military goods) the investment-to-GDP ratio in 2010 is now 20.5 percent instead of 15.6 percent. The demand side growth continues to post a remarkable uptick in investment. Investment grew by 37 percent year-on-year and contributed 6.8 percentage points to GDP growth, mostly driven by durable equipment and private construction. Private construction grew by 22 percent, albeit at a slower pace than the preceding three quarters, and compensated for the contraction in public construction which shrank by 37.3 percent due to continued fiscal tightening and a high base effect. Investment in durable equipment grew 17 percent with the building up of inventory in industrial machineries and road vehicles.